Dampak Stres Terhadap Kinerja Karyawan pada Sektor F&B dan Keuangan - Ludfiah Zahrah; Lingga Yuliana (PPIMAN Pusat Publikasi Ilmu Manajemen, 2025)
This study aims to see how significant the impact of work stress experienced on employee performance and the method used in this study is a qualitative approach method. The sample collection technique uses purposive sampling where the respondents are two people from different work sectors. Based on the results of the research that has been done is very significant and quite a big impact because when a person experiences stress at work, a decrease in performance will occur so that the company must pay more attention to its employees so that the impact of stress at work is not increasingly detrimental both individually and the company's reputation.